Perancangan Antena Metamaterial Superstrate Untuk Meningkatkan Gain Dan Bandwidth Pada Mimo Microstrip Patch Array Untuk Jaringan 5G - Johanes Firdaus; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In recent years, research on microstrip antennas is increasingly being develoved for the needs of inovations, performance, and better efficiency improvements in upcoming 5G wireless communication. Inthis research, a microstrip antenna is designed by using metamaterial superstrate which operates at 38 GHz communication to increase gain and bandwidth in antenna. The design have been simulated using CSTMicrowave Studio. The dimension used in the metamaterial superstrate layer are 4.8 × 10 mm. Simulation results show that the antenna design using the metamaterial superstrate can increase bandwidth up to 1.05GHz and gain increase up to 1.8 dBi. In this design, it was later design a MIMO 4×4 with patch distance of 1.98 mm and increase gain up to 5.2 dBi. The use of metamaterial superstrate techniques has the potential tobe used in various communication aplications.Keyword : Antenna, Gain, Metamaterial, Microstrip, Superstrate.